2018
DOI: 10.1002/hep.29597
|View full text |Cite
|
Sign up to set email alerts
|

Partial splenic artery embolization for severe hepatic myelopathy in cirrhosis

Abstract: Hepatic myelopathy (HM) is a devastating but rare complication of cirrhosis and portal hypertension that profoundly affects quality of life and improves only with liver transplantation. We present a case where progressive severe spastic paraparesis due to HM was substantially reversed with partial splenic artery emobilization (PSAE). (Hepatology 2018;67:1169-1171).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Shunt limiting is preferred, as total shunt occlusion might have a higher risk of adverse events related to the rapid increase of portal hypertension. Moreover, Philips et al [ 22 ] reported partial splenic artery embolization (PSAE) for a patient with HM. Neurological function improved rapidly and constantly after PSAE.…”
Section: Discussionmentioning
confidence: 99%
“…Shunt limiting is preferred, as total shunt occlusion might have a higher risk of adverse events related to the rapid increase of portal hypertension. Moreover, Philips et al [ 22 ] reported partial splenic artery embolization (PSAE) for a patient with HM. Neurological function improved rapidly and constantly after PSAE.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic criteria of HM included 1821 : (1) a history of chronic liver disease and underwent TIPS treatment; (2) progressive spastic paraplegia, without obvious sphincter and shallow sensory dysfunction; (3) no symptom of spastic paraplegia before TIPS; and (4) normal cerebrospinal fluid and serum blue copper protein, no Kayser-Fleischer ring. Exclusion criteria of HM included 1821 : (1) spinal cord lesions caused by spinal cord space-occupying mass, multiple sclerosis, hepatolenticular degeneration, infectious, inflammatory, autoimmune, vascular, hereditary, and metabolic causes; (2) severe hepatorenal damage; (3) severe infection and systemic cachexia; (4) serious cardiovascular diseases; and (5) cardiac portal hypertension.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria of HM included 1821 : (1) spinal cord lesions caused by spinal cord space-occupying mass, multiple sclerosis, hepatolenticular degeneration, infectious, inflammatory, autoimmune, vascular, hereditary, and metabolic causes; (2) severe hepatorenal damage; (3) severe infection and systemic cachexia; (4) serious cardiovascular diseases; and (5) cardiac portal hypertension.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…105 Individual case reports describe improvement with portosystemic shunt occlusion, 111 hepatitis C treatment, 112 and partial splenic artery embolization. 113 Liver transplantation has shown the most promising results in reversing this otherwise invariably progressive syndrome. 105,114,115 Transplantation is most beneficial when performed in the early stage of the disease.…”
Section: Hepatic Myelopathymentioning
confidence: 99%